From soil pollution to "cadmium rice” to public health impacts: An interdisciplinary analysis of influencing factors and possible responses - Holdaway, J; Wuyi, W (Institute of Geographic Sciences and Natural Resources Research, Chinese Academy of Sciences, 2018)
This article discusses the causes of the contamination of rice with cadmium in China and considers what we know about the severity of the problem. It argues that it is misleading to extrapolate simply from levels of cadmium in soil to health risks, because the uptake of cadmium by crops and the health impacts of the metal are affected by multiple factors. These include not only background levels of cadmium and pollution from mining and industry, but also soil quality, climatic conditions and the type and variety of crops grown. Social and cultural factors, including dietary habits, other exposure sources, nutritional quality and general health status will also affect the intake of cadmium and the severity of health impacts. For these reasons we argue that interdisciplinary analysis is crucial to a better understanding of patterns of risk to health from cadmium pollution, and to the design of effective responsive measures.